Memory and Technology How We Use Information in the Brain and the World - Finley, Jason R. (Springer International Publishing, 2018)
How is technology changing the way people remember? This book explores the interplay of memory stored in the brain (internal memory) and outside of the brain (external memory), providing a thorough interdisciplinary review of the current literature, including relevant theoretical frameworks from across a variety of disciplines in the sciences, arts, and humanities. It also presents the findings of a rich and novel empirical data set, based on a comprehensive survey on the shifting interplay of internal and external memory in the 21st century. Results reveal a growing symbiosis between the two forms of memory in our everyday lives. The book presents a new theoretical framework for understanding the interplay of internal and external memory, and their complementary strengths. It concludes with a guide to important dimensions, questions, and methods for future research. Memory and Technology will be of interest to researchers, professors, and students across the disciplines of psychology, philosophy, library and information science, human factors, media and cultural studies, anthropology and archaeology, photography, and cognitive rehabilitation, as well as anyone interested in how technology is affecting human memory. _____ "This is a novel book, with interesting and valuable data on an important, meaningful topic, as well as a gathering of multidisciplinary and interdisciplinary ideas...The research is accurately represented and inclusive. As a teaching tool, I can envision graduate seminars in different disciplines drawing on the material as the basis for teaching and discussions." Dr. Linda A. Henkel, Fairfield University "This book documents the achievements of a vibrant scientific project - you feel the enthusiasm of the authors for their research. The organization of the manuscript introduces the reader into a comparatively new field the same way as pioneering authors have approached it." Prof. Dr. Wolfgang Schönpflug, Freie Universität Berlin.